(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
In this article, the author conducted a small analysis of the essence and role of the religion of Islam in modern society. The purpose of this article is to reveal the historical facts of the development of Islam over many centuries. And at the end, the author provides proposals for the interim results of his work.